Green Innovation: Trend Research Using Bibliometric Analysis - Nuryakin, Nuryakin (Jurnal Manajemen Bisnis, 2023)
Research aims: This study aims to explore and analyze research trends in green innovation. A literature review was used in this study by conducting a bibliometric analysis of green innovation by measuring research trends on green innovation in the last five years. This study also performed descriptive data and analysis on research trends and proposed an agenda for further studies on green innovation. Design/Methodology/Approach: This study approach carried out bibliographical analysis by taking the Scopus Database. Then filtering research articles was carried out in the 2019 – 2021 period. Bibliometric analysis techniques, citation analysis, and co-citation analysis were also conducted.Research findings: This study revealed the nature and direction of research that the green innovation field has undertaken over the past five years. Five clusters existed as themes that appeared in the green innovation literature.Theoretical Contribution/Originality: The theoretical implications of this study provide several important arguments for contributions to the field of green innovation and also contribute to several studies, journals, and institutions that have established studies in this field. Practitioners/Policy Implications: This study contribution to the most influential authors, institutions, and countries related to research on green innovation with possible future research directions.Research Limitations/Implications: This study has provided valuable opportunities to focus on studies only within the scope of green innovation. This study also has contribution to knowledge by considering suggestions for further research.